CONSEPTUAL MODEL APPLICATION OF KNOWLEDGE DIMENSION COMPLEXITY AND COGNITIVE PROCESS LEVEL IN STATIC FLUID MATERIALS IN HIGH SCHOOL PHYSICS LEARNING - Fera Desnawati; Amali Putra; - Gusnedi; - Hidayati (Universitas Negeri Padang, 2022)
The 2013 curriculum requires the implementation of learning activities by referring to the Bloom classification revised by Anderson and Krathwohl (2001), which combines knowledge dimensions and cognitive process levels. However, the complexity of the knowledge dimension and the realization of the cognitive processing level in static fluid materials have not been optimally realized. This research aims to establish a conceptual model of the complexity of the knowledge dimension and cognitive process level of static fluid materials in high school physics learning. The type of research is R&D research using the ADDIE development method, which is reduced to the development stage. The subjects were 3 lecturers from FMIPA UNP in the Department of Physics and 3 physics teachers from Merangin Regency State High School, including SMAN 3, 6, and 17 Merangin. The object is learning tools (RPP, teaching materials, and evaluation instruments) oriented to knowledge dimension and cognitive process level in static fluid materials in high school physics learning. The expert group's research and application results on the knowledge dimension complexity and cognitive process hierarchical conceptual model composed of teaching plans, teaching materials, and evaluation tools were 0.71, and the practitioner group was 0.87. The average result of the degree of learning device verification value is 0.79, so it can be classified as effective and practical to test the effectiveness and practicality of this field.